The Implementation of End User Computing Satisfaction and Delone & Mclean Model to Analyze User Satisfaction of M.TIX Application - Pramudito, Dendy K; Arijanti, Susi; Yanto RUkmana, Arief; Oetomo, Dedy Setyo; Kraugusteeliana, Kraugusteeliana (Jurnal Informasi dan Teknologi, 2023)
This study aims to identify the elements that affect user satisfaction and the degree of user satisfaction with the online ticket application. This study makes use of the End User Computing Satisfaction (EUCS) model's development model, which includes three DeLone and McLean variables system quality, information quality, and service quality along with five EUCS model variables: content, accuracy, format, timeliness, and ease of use. The population of this study is made up of frequent users of Android-based online ticketing applications. Respondents were selected from as many as 175 respondents to be the research sample using the purposive sampling technique. Data analysis was carried out using the PLS-SEM approach with SmartPLS tools. The results showed that users were satisfied using the online ticket application, and out of eight hypotheses, two were rejected and 6 were accepted. So that the factors that influence user satisfaction in online ticket applications are accuracy, ease of use, timeliness, system quality, information quality, and service quality.